Structural Design and Impact Analysis of Deployable Habitat Modules - Yihong Hong; Wenjuan Yao; Yan Xu (International Journal of Aerospace Engineering)
Space-deployable habitat modules provide artificial habitable environments for astronauts and will be widely used for the construction of future space stations and lunar habitats. A novel structural design concept of space-deployable habitat modules consisting of flexible composite shells and deployable trusses has been proposed. Geometric relationships of deployable trusses based on two types of scissor elements were formulated. Flexible composite shells of space habitat modules were designed, and a nonlinear FEA model using ANSYS software was described. Considering folding efficiencies, stiffness, and strength of the structures, the influences of design parameters were analyzed and the final design scheme of space-deployable habitat modules was determined. After detailing the structural designs, low-speed impact dynamic responses between the structures and a stainless steel cylinder were simulated. The analysis results show that dynamic responses are only significant at the point of low-speed impact. The works will provide technical supports for structural designs and engineering applications of space-deployable habitat modules.